Zagorsk Experiment and the Fate of the Scientist. In Memory of A.V. Suvorov (1953 — 2024) - Sorokin, V.M.; Darinskaia, L.A.; Molodtsova, G.I.; Demyanchuk, R.V. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2024)
The article, based on a study of scientific materials, examines the activities of Alexander V. Suvorov (1953-2024), a Doctor of Psychology, Professor, and the world's only deafblind psychologist, researcher, teacher, philosopher, and poet. His biography is inextricably linked to the study of deafblind individuals in our country, particularly through an experiment involving the training of four pupils from the Zagorsk boarding school at the Faculty of Psychology of Moscow State University from 1972 to 1977. Educating deafblind individuals in the USSR required long-term efforts from defectologists, teachers, and psychologists. The establishment of a boarding school for deafblind children in Zagorsk in 1963 significantly improved the circumstances for this group of individuals, providing them with pathways to full development, social and professional adaptation, and creative self-expression. Four graduates of the Zagorsk boarding school practically validated the scientific theories of Vygotsky, Sokolyansky, Meshcheryakov, and Ilyenkov. The biography of A.V. Suvorov, who made a unique contribution to the development of typhlosurdopsychology as a branch of special psychology, is particularly noteworthy. The scientist was especially interested in the social environment of deafblind individuals, the nature of self-realization, and the sometimes complex relationships they developed with sighted and hearing individuals. В статье на основе исследования научных материалов рассматривается деятельность Александра Васильевича Суворова (1953-2024), доктора психологических наук, профессора, единственного в мире слепоглухого психолога, педагога, философа и поэта. Его биография неразрывно связана с экспериментом по обучению четверых воспитанников Загорского детского дома на факультете психологии МГУ с 1971 по 1977 г. До этого периода известны были только отдельные случаи достижения слепоглухими высокого уровня интеллектуально-культурного развития (Е. Келлер, США, О.И. Скороходова, СССР). Такие результаты считались исключениями и относились в большей степени к категории случайного сочетания различных благоприятствующих факторов. Именно поэтому обучение слепоглухих в СССР потребовало длительных усилий специалистов в этой области - дефектологов, психологов, педагогов. Открытие в Загорске детского дома для слепоглухих детей в 1963 г. изменило положение этой группы инвалидов, указав им путь социальной и профессиональной адаптации, самореализации, творческого самовыражения. Четверо выпускников детского дома на практике подтвердили правильность научных взглядов Выготского, Соколянского, Мещерякова, Ильенкова. Особенно выделяется биография А.В. Суворова, внесшего свой вклад в развитие тифлосурдопсихологии как отрасли специальной психологии. Больше всего ученого интересовало социальное пространство слепоглухого человека, характер его самореализации, складывающиеся порой драматические отношения со зрячими и слышащими. В настоящее время результаты его исследований требуют переосмысления применительно к психологическим и педагогическим задачам общего образования, ставшего инклюзивным.